2018
DOI: 10.1016/j.ctcp.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Participant characteristics of users of holistic movement practices in Australia

Abstract: As a group, Australian users of holistic movement practices differ on a range of characteristics from those Australians active in other types of physical activities. However, differences between yoga/Pilates and t'ai chi/qigong users suggest these practices attract somewhat different sub-populations. To what extent these differences are due to characteristics inherent to the practices themselves or to differences in delivery-related parameters needs to be examined in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…While the effects of mindfulness-based interventions on mental health have been systematically examined (Goldberg et al, 2018;Hofmann et al, 2010;Kuyken et al, 2016), there is a lack of research on the prevalence, patterns and predictors of mindfulness use across sociodemographic and political groups in the general population. The survey research to date has mostly focused on the prevalence of mind-body practices (yoga, tai chi, qigong and meditation) and has generally been based on nationally representative samples in Australia (Penman et al, 2012;Sibbritt et al, 2011;Steel et al, 2018;Vergeer et al, 2017Vergeer et al, , 2018 and the United States (Birdee et al, 2008(Birdee et al, , 2009Burke et al, 2017;Cramer et al, 2016aCramer et al, , 2016bKachan et al, 2017;Lauche et al, 2016;Olano et al, 2015;Park et al, 2015;Upchurch and Johnson, 2019;Wolsko et al, 2004), where statistically significant differences have been observed based on age, gender, marital status, education and household income.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of mindfulness-based interventions on mental health have been systematically examined (Goldberg et al, 2018;Hofmann et al, 2010;Kuyken et al, 2016), there is a lack of research on the prevalence, patterns and predictors of mindfulness use across sociodemographic and political groups in the general population. The survey research to date has mostly focused on the prevalence of mind-body practices (yoga, tai chi, qigong and meditation) and has generally been based on nationally representative samples in Australia (Penman et al, 2012;Sibbritt et al, 2011;Steel et al, 2018;Vergeer et al, 2017Vergeer et al, , 2018 and the United States (Birdee et al, 2008(Birdee et al, , 2009Burke et al, 2017;Cramer et al, 2016aCramer et al, , 2016bKachan et al, 2017;Lauche et al, 2016;Olano et al, 2015;Park et al, 2015;Upchurch and Johnson, 2019;Wolsko et al, 2004), where statistically significant differences have been observed based on age, gender, marital status, education and household income.…”
Section: Introductionmentioning
confidence: 99%
“…An issue here could also be that these types of events may attract certain groups of people in their present format, perhaps those who are more health-conscious or those who had previously experienced problems with alcohol, and are specifically looking for an alternative. Although we do not yet have data about what groups of people attend conscious clubbing events, Vergeer et al, (2018) found that people engaged in similar holistic movement practices in Australia were more likely to be older, female, and had higher levels of education than those who did not participate.…”
Section: Survey Limitationsmentioning
confidence: 79%
“…This may also indicate an association with less traditional lifestyles. Positive associations with percentages of women and university degrees echo participant characteristics of the more established traditional Eastern HMPs [ 20 , 22 , 23 ], tentatively suggesting that other HMPs may cater to similar population subgroups. It remains to be established whether the neighbourhood socio-demographics of HMP-offering areas are indeed reflective of participant socio-demographics, but it seems a reasonable possibility.…”
Section: Discussionmentioning
confidence: 94%
“…In this paper, we attempted to shed some light on the provision of HMPs—forms of physical activity embedded in holistic philosophies of well-being [ 5 ]. While the traditional Eastern HMPs such as Yoga and Tai Chi have become relatively well established within the landscape of physical activities in modern-day societies, and participation parameters of these practices have been researched as forms of physical activity [ 21 , 22 ] or complementary medicine [ 19 , 44 ], a range of newer Western-born HMPs also exist, about which very little is known. In this study, we focused on provision, as this is, although not sufficient, at least a necessary precondition to enable participation in HMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation